2010
DOI: 10.4236/health.2010.29158
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein as a marker of cardiovascular risk in obese children and adolescents

Abstract: Background and aim of the work: High-sensiti- vity C-reactive protein (hsCRP) is a marker of low grade inflammatory state, which characterises an atherosclerotic process. The metabolic syndrome is associated with insulin resistance and a systemic low-grade inflammatory state. These disorders may arise at a very early age in obese children. We aimed to assess the utility of (hsCRP) as a marker of cardiovascular risk in obese children and adolescents. Patients and methods: This study was conducted on 100 obese c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
3
3
0
1
Order By: Relevance
“…Our results were in alignment with previous studies, demonstrating that obese children had elevated inflammatory markers, for instance hs-CRP 8 25 26 27 28 29 30 31 32) , TNF-α 26 27 29 33) , and IL-6 26 , 28 , 34) . Compared to the study done by El-shorbagy and Ghoname 25) demonstrating a prevalence of hs-CRP>3 mg/L of 35%, our study showed as much as twice higher prevalence. Unfortunately, we could not identify MetS as a potential risk for increasing the selected inflammatory cytokines even though there was a report to that effect 35) .…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in alignment with previous studies, demonstrating that obese children had elevated inflammatory markers, for instance hs-CRP 8 25 26 27 28 29 30 31 32) , TNF-α 26 27 29 33) , and IL-6 26 , 28 , 34) . Compared to the study done by El-shorbagy and Ghoname 25) demonstrating a prevalence of hs-CRP>3 mg/L of 35%, our study showed as much as twice higher prevalence. Unfortunately, we could not identify MetS as a potential risk for increasing the selected inflammatory cytokines even though there was a report to that effect 35) .…”
Section: Discussionsupporting
confidence: 92%
“…9 CRP merupakan prediktor yang kuat untuk penyakit kardiovaskuler dengan pengukuran yang sederhana, lebih murah, terstandar, dan tersedia secara luas. 10 Kadar CRP yang tinggi dapat dipengaruhi oleh beberapa faktor, diantaranya adalah sindrom metabolik, faktor risiko sindrom metabolik, aktivitas fisik, dan asupan makanan.…”
Section: Pendahuluanunclassified
“…Another study by El-Shorbagy et al also reported 12.7% of the subjects that did not display MetS had hsCRP levels > 3 mg/dL (17). While, these data question the value of using hsCRP in the assessment of MetS, more research is needed in this young adult population in order to assess the value of including hsCRP measures alongside traditional MetS criteria.…”
Section: Mets Components and Hscrp Levelsmentioning
confidence: 99%
“…Researchers have also linked pro-inflammatory states to the onset of IR (14,15) as well as the development of atherosclerosis (16)(17)(18)(19). C-reactive protein (CRP), a biomarker of inflammation, has recently emerged as an important predictor of MetS, T2DM as well as CVD (10).…”
Section: Metabolic Syndrome (Mets)mentioning
confidence: 99%
See 1 more Smart Citation